Central Pattern Generator In Bio-Inspired Robot: Simulation Using MATLAB - Kassim, Muhammad Hafiz; Zainal, Norzeti; Arshad, Mohd Rizal (Universiti Sains Malaysia, 2008)

(untitled)
Central pattern generator (CPG) is defined here as a neural network responsible for the production of the timing cues of a rhythmic motor output pattern. In biological system, the CPG is a network of neurons that generate the rhythmic movements such as locomotion of animals.